Ongoing grounding line retreat and fracturing initiated at the Petermann Glacier ice shelf, Greenland, after 2016 - Millan, Romain; Mouginot, Jeremie; Derkacheva, Anna; Rignot, Eric; Milillo, Pietro; Ciraci, Enrico; Dini, Luigi; Bjørk, Anders (The Cryosphere, 2022)
International audience The Petermann ice shelf is one of the largest in Greenland, buttressing 4 % of the total ice sheet discharge, and is considered dynamically stable. In this study, we use differential synthetic aperture radar interferometry to reconstruct the grounding line migration between 1992 and 2021. Over the last 30 years, we find that the grounding line of Petermann retreated 4 km in the western and eastern sectors and 7 km in the central part. The majority of the retreat in the central sector took place between 2017 and 2021, where the glacier receded more than 5 km along a retrograde bed grounded 500 m below sea level. While the central sector stabilized on a sill, the eastern flank is sitting on top of a down-sloping bed, which might enhance the glacier retreat in the coming years. This grounding line retreat followed a speedup of the glacier by 15 % in the period 2015–2018. Along with the glacier acceleration, two large fractures formed along flow in 2015, splitting the ice shelf in three sections, with a partially decoupled flow regime. While these series of events followed the warming of the ocean waters by 0.3 ∘C in Nares Strait, the use of a simple grounding line model suggests that enhanced submarine melting may have been responsible for the recent grounding line migration of Petermann Glacier.